Women's Movement in Formal Education (Case Study in Aewora Village, Ende Regency) - Zainur Wula (Universitas Muhammadiyah Palu, 2025)
Education is one of the manifestations of human rights in an effort to permanently liberate ignorance, poverty, and social inequality. Efforts to improve human resources through formal education in Indonesia are mandated by the 1945 Constitution, Law No. 20 of 2003 concerning the national education system and Law No. 12 of 2012 concerning higher education. Since Indonesia became independent in 1945 and entered the age of 79 years, formal education has not been evenly distributed in Aewora village as an integral part of Indonesia. Discrimination and socio-cultural oppression of women's formal education still occur and for many years women have fought for their rights to obtain formal education on an equal footing with men. For many years, women in Aewora village could only enjoy elementary and junior high school education, while at the high school level it was very limited, as was higher education. Women's struggles can be seen in 2020, 2021, 2022, 2023, 2024, namely at the high school and tertiary education levels, starting to appear in limited numbers. Slowly, oppression, negative stereotypes on women's formal education began to open up the awareness of the thinking by traditional family and community leaders that education has an important role in improving the quality of human resources and realizing a better quality of life. The backwardness of women's formal education in Aewora is caused by strong customs, and patriarchy that places men in the top and superior positions in various fields, so that women work more in housekeeping, marry at a young age and still consider women to be physically very weak and unable to travel far. This socio-cultural construction causes women to be underdeveloped and oppressed in the field of formal education.